Quantum-chemical study of nitrogen and magnesium co-doping in ?-Cr2O3 - Stashans, A. (2016)
© 2016 World Scientific Publishing Company.Study of corundum-type chromium oxide (?-Cr2O3) crystal doped with the nitrogen and magnesium impurities has been carried out through the use of first-principles calculations based on the density functional theory (DFT) and generalized gradient approximation (GGA). Three cases corresponding different impurity-impurity distances have been considered. Structural, electronic and magnetic properties have been studied for all co-doping cases. The p-type electrical conductivity was found when distance between the Mg and N atoms is equal to 4.10 . The results obtained are consistent with the available experimental data.